Lessons from the pandemic: Responding to emerging zoonotic viral diseases—a Keystone Symposia report. Issue 1 (2nd October 2022) - Cable, Jennifer; Fauci, Anthony; Dowling, William E.; Günther, Stephan; Bente, Dennis A.; Yadav, Pragya Dhruv; Madoff, Lawrence C.; Wang, Lin‐Fa; Arora, Rahul K.; Van Kerkhove, Maria; Chu, May C.; Jaenisch, Thomas; et al.
Abstract: The COVID‐19 pandemic caught the world largely unprepared, including scientific and policy communities. On April 10–13, 2022, researchers across academia, industry, government, and nonprofit organizations met at the Keystone symposium "Lessons from the Pandemic: Responding to Emerging Zoonotic Viral Diseases" to discuss the successes and challenges of the COVID‐19 pandemic and what lessons can be applied moving forward. Speakers focused on experiences not only from the COVID‐19 pandemic but also from outbreaks of other pathogens, including the Ebola virus, Lassa virus, and Nipah virus. A general consensus was that investments made during the COVID‐19 pandemic in infrastructure, collaborations, laboratory and manufacturing capacity, diagnostics, clinical trial networks, and regulatory enhancements—notably, in low‐to‐middle income countries—must be maintained and strengthened to enable quick, concerted responses to future threats, especially to zoonotic pathogens. Abstract : The COVID‐19 pandemic caught the world largely unprepared, including scientific and policy communities. On April 10–13, 2022, researchers across academia, industry, government, and nonprofit organizations met at the Keystone symposium "Lessons from the Pandemic: Responding to Emerging Zoonotic Viral Diseases" to discuss successes and challenges of the COVID‐19 pandemic and what lessons can be applied moving forward.